Clinical Profile, Laboratory Profile and Current Antibiotic Sensitivity Pattern of Enteric Fever in a Teaching Hospital of Central Nepal - Pan, Atanu; Jana, Debarshi (Journal of College of Medical Sciences-Nepal, 2020)
Background: About 26.9 million typhoid cases and more than 2 lakh deaths occur each year, with majority of the cases reported in Asia. The incidence of typhoid varies substantially within Asia. The aim of the study is to asses study the clinical and laboratory profile, culture positive & sensitivity pattern of Salmonella Typhiand its response to antimicrobial therapy in the paediatric department of College Of Medical Sciences, Bharatpur, Nepal. Methods: A descriptive cross sectional study was conducted among 104 Children in the age group of 5 to 12 years admitted with history of fever ≥5 days duration chosen as study population Paediatric Department College Of Medical Sciences, Bharatpur, Nepal from February 2015 to October 2019. Results: Our study found that 40(38.5) patients had pallor, 28(26.9) patients had Hepatomegaly, 19(18.3) patients had splenomegaly and 21(20.2) patients had coated tongue. It was found that 37(90.2) patients had sensitive ciprofloxacin, 37(90.2) patients had sensitive ofloxacin, 39(95.1) patients had sensitive levofloxacin and 37(90.2) patients had sensitive azithromycin. 38(92.7) patients had sensitive Cefixime, 38(92.7) patients had sensitive ceftriaxone, 39(95.1) patients had sensitive imipenam and 33(80.5) patients had sensitive cotrimoxazole ,32(78.0) patients had sensitive amoxicillin, 37(90.2) patients had sensitive cefotaxime. Conclusions: Enteric fever is an important cause of febrile illness in children. Fever with anorexia, cough, diarrhea, headache, hepatosplenomegaly were the common clinical manifestations of enteric fever. An adequate trial of first line antibiotics like oral cefexime,ofloxacin,co-trimoxazole, ampicillin can be tried before starting injectable antibiotics due to increased emergence of sensitivity to these drugs. Keywords: enteric fever; antibiotic sensitivity pattern